2009
DOI: 10.1103/physreve.79.031121
|View full text |Cite
|
Sign up to set email alerts
|

Direct evidence for conformal invariance of avalanche frontiers in sandpile models

Abstract: Appreciation of stochastic Loewner evolution (SLE_{kappa}) , as a powerful tool to check for conformal invariant properties of geometrical features of critical systems has been rising. In this paper we use this method to check conformal invariance in sandpile models. Avalanche frontiers in Abelian sandpile model are numerically shown to be conformally invariant and can be described by SLE with diffusivity kappa=2 . This value is the same as value obtained for loop-erased random walks. The fractal dimension and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 50 publications
3
34
0
Order By: Relevance
“…Shcramm-Loewner evolution (SLE), as a technique to process the geometrical properties of 2D critical models, has been helpful as well as CFT to uncover the geometrical aspects of this model. It has been shown that 2D BTW model is SLE with diffusivity parameter κ = 2, i.e., SLE 2 [17]. This result is consistent with the CFT predictions, i.e., the relation between SLE and CFT c = (6−κ)(3κ−8) 2κ [18].…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Shcramm-Loewner evolution (SLE), as a technique to process the geometrical properties of 2D critical models, has been helpful as well as CFT to uncover the geometrical aspects of this model. It has been shown that 2D BTW model is SLE with diffusivity parameter κ = 2, i.e., SLE 2 [17]. This result is consistent with the CFT predictions, i.e., the relation between SLE and CFT c = (6−κ)(3κ−8) 2κ [18].…”
Section: Introductionsupporting
confidence: 80%
“…It is easy to see that in any wave, the set of toppled sites forms a connected cluster with no voids (untoppled sites fully surrounded by toppled sites), and no site topples more than once in one wave. Geometrical aspects of this model have been the subject of intense studies recently [17,23,24]. One example is the exterior perimeter of an avalanche or a wave that is numerically shown to be loop-erased random walk (LERW) in two dimensions [17,23].…”
Section: A Wavesmentioning
confidence: 99%
“…In 2010, Smirnov was awarded the Fields medal for the proof of conformal invariance of percolation and the planar Ising model in statistical physics. SLE has soon found many applications and turned out to describe the vorticity lines in turbulence [26,86], domain walls of spin glasses [87,88,89], the nodal lines of random wave functions [90,91], the iso-height lines of random grown surfaces [92,93,94,95,96,97], the avalanche lines in sandpile models [98] and the coastlines and watersheds on Earth [99,101,102]. Among which, SLE could provide quite unexpected connections between some features of interacting systems and ordinary uncorrelated percolation [26,90].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, numerically correspondence has been shown for a large number of models as mentioned above. It has been argued that SLE can be applied to models exhibiting nonself-crossing paths on a lattice, showing self-similarity, not only in equilibrium but also out of equilibrium as the example discussed here [8,22,23]. In random discretized landscapes each site is characterized by a real number such as, e.g., the height in an elevation map, the intensity in a pixelated image, or the energy in an energy landscape [14].…”
mentioning
confidence: 99%